Respuesta :

Answer:

y= -6

x=14

Step-by-step explanation:

in attachment

Ver imagen SLAlson
Ver imagen SLAlson

Answer: (5,3)

Step-by-step explanation:

Solve by Addition/Elimination

x + y = 8

3x − y = 12

Add the two equations together to eliminate y from the system.

    x + y = 8

+ 3x −y = 12

  4x      = 20

Divide each term in 4x = 20 by 4.

4x  = 20

4      4

Cancel the common factor of 4.

x= 20/4

x = 5

Substitute the value found for x into one of the original equations to solve for y.

  (5) + y = 8

Remove parentheses.

  5 + y = 8

Move all terms not containing y to the right side of the equation.

Subtract 5 from both sides of the equation.

  y = 8 − 5

Subtract 5 from 8.

  y = 3

The solution to the independent system of equations can be represented as a point.

  (5, 3)

The result can be shown in multiple forms.

Point Form:

  (5, 3)

Equation Form:

  x = 5, y = 3

Ver imagen drazo18